The Effect of Google Classroom in Improving Students' Grammar Competence - Amrizal Amrizal (Institut Agama Islam Negeri Palopo, 2022)
The study examined the effect of Google Classroom on students' grammatical competence. The experiment was followed by a test. The group that received therapy was the experimental group, whereas the control group received no treatment. Using SPSS, the T-test was used to determine if the pre- and post-test scores of the control and experimental groups differed significantly. The results of the investigation were 1). the pre- and post-test mean scores for the control and experimental groups differ considerably. This indicates that the use of Google Classroom greatly improved students' Ekonomi Syariah performance in present grammar from excellent to very good. 2). the post-test mean scores of the control and experimental groups vary significantly. The usage of Google Classroom had a considerable impact on the test performance of the experimental group in particular.